2013
DOI: 10.1073/pnas.1212729110
|View full text |Cite
|
Sign up to set email alerts
|

Assessing what to address in science communication

Abstract: As members of a democratic society, individuals face complex decisions about whether to support climate change mitigation, vaccinations, genetically modified food, nanotechnology, geoengineering, and so on. To inform people's decisions and public debate, scientific experts at government agencies, nongovernmental organizations, and other organizations aim to provide understandable and scientifically accurate communication materials. Such communications aim to improve people's understanding of the decision-relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 224 publications
(165 citation statements)
references
References 71 publications
3
162
0
Order By: Relevance
“…Failure to understand immune processes in individuals' bodies, or vectors within groups, precludes any appreciation of the social good of high vaccination rates (41). Such results reveal gaps in understanding and misconceptions that might impede decision making, which a prescriptive narrative should address (38,39). Interview transcripts provide insights into natural wording, contexts, and metaphors that will make the resulting narrative most useful and meaningful to the target audience, precisely because the narrative will feel familiar and use concepts that are commonly understood (42,43).…”
Section: Prescriptive Scientific Narrativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to understand immune processes in individuals' bodies, or vectors within groups, precludes any appreciation of the social good of high vaccination rates (41). Such results reveal gaps in understanding and misconceptions that might impede decision making, which a prescriptive narrative should address (38,39). Interview transcripts provide insights into natural wording, contexts, and metaphors that will make the resulting narrative most useful and meaningful to the target audience, precisely because the narrative will feel familiar and use concepts that are commonly understood (42,43).…”
Section: Prescriptive Scientific Narrativesmentioning
confidence: 99%
“…This approach is particularly useful for revealing gaps in knowledge and misunderstandings that need to be rectified (38). In essence, this approach compares the expert model of a given domain to a descriptive model of people's actual understanding.…”
Section: Prescriptive Scientific Narrativesmentioning
confidence: 99%
“…Experts sometimes resist the use of plain language, because they don't want to appear to talk down to their audience members (Bruine de Bruin and Bostrom 2013 (Davis et al 2006;Smith et al 2008). …”
Section: Struggles To Meet the Maxim Of Mannermentioning
confidence: 99%
“…Although surveys can easily be conducted with large sample sizes, semi-structured interviews are needed to inform their design (Bruine de Bruin and Bostrom 2013). Indeed, surveys should include questions about the topics that experts deemed relevant (as identified in the normative research) and that non-experts deemed relevant (as identified in the interviews), in wording that the interviewees used in the interviews.…”
Section: Follow-up Public Perception Surveysmentioning
confidence: 99%
See 1 more Smart Citation